Generation of an induced pluripotent stem cell line (DHMCi009-A) from an individual with TUBB2A tubulinopathy - Schröter, Julian; Syring, Hanna; Göring, Gudrun; Kölker, Stefan; Opladen, Thomas; Hoffmann, Georg F.; Syrbe, Steffen; Jung-Klawitter, Sabine (Stem cell research, 2022)
TUBB2A tubulinopathy is a rare neurodevelopmental disorder with developmental delay, epilepsy, and less frequent malformations of cortical development compared to other tubulinopathies. Peripheral blood mononuclear cells (PBMCs) from a male subject harboring the heterozygous de novo TUBB2A variant c.[743C>T] (p.[Ala248Val]) were reprogrammed to induced pluripotent stem cells (iPSCs) using the CytoTune™-iPS 2.0 Sendai Reprogramming Kit (Invitrogen). Generated iPSCs showed a normal karyotype, expression of pluripotency markers, spontaneous in vitro differentiation in all three germ layers, and are a suitable human disease model to analyze pathomechanisms underlying TUBB2A tubulinopathy and potential therapeutic targets.